Immersive Technologies: challenges of the inclusive design in times of natural hazards and climate change - Tavares, Daniela Cardoso; Guarese, Renan Luigi M. M.; Cheiran, Jean Felipe P.; Teófilo, Mauro Ricardo da S. (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR); 2024: Anais Estendidos do XXVI Simpósio de Realidade Virtual e AumentadaDO - 10.5753/svr_estendido.2024.243116, 2024)
This paper addresses inclusive design in immersive technologies. From this perspective, we intend to expand the discussion on inclusive design among researchers and developers of immersive technologies. In addition, we intend to promote reflection on the importance of implementing inclusive design in projects involving climate change awareness and natural hazard mitigation. From the development of this research, we realized that, in general, the contributions of accessibility guidelines, inclusive design principles, and the research agenda represent a solid basis for discussing the opportunities and challenges related to the use of immersive technologies in emergency situations, ensuring that they do not exclude people with disabilities.